Tindak Tutur Direktif Wacana Berita Online: Kajian Media Pembelajaran Berbasis Teknologi Digital - Waljinah, Sri; Prayitno, Harun Joko; Purnomo, Eko; Rufiah, Ani; Kustanti, Erry Widya (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This study aims to identify directive speech acts on online news titles. Research data are sentences in online news titles. Research data sources in the form of online news titles sourced from the news in CNN Indonesia, Liputan 6.com, Detiknews, Viva.co.id.news, TEMPO.CO, Kompas.com, Kumparan.News, and Republika.co.id. Data collection using documentation methods, see, and note technique. Analysis of research data using the intralingual and pragmatic matching methods. The validity of the data in this study uses the triangulation method. The results showed the directive speech acts in the online news titles included: (1) forcing as much as 3.2%; (2) request as much as 4%; (3) asking for 40%; (4) giving orders as much as 2.4%; (5) demanded 4.8%; (6) prohibiting 12.8%; (7) suggest 11.2%; (8) invite 16%; and (9) collect 5.6%. The directive speech act on the online news headline can be used as a learning medium in digital technology-based schools.Keywords: directive speech acts; online news; learning media; digital technology.